O uso das alegorias como mecanismos de subversão em o espelho das almas simples, de Marguerite Porete - Alves, Yasmin de Andrade (2022)
The works of female authorship produced in the context of the Low Middle Ages play considerable roles in the formation of a feminist consciousness and demands around social restructuring. Considering the propagation of feminine mysticism in this period, this work has as its object of study the work The Mirror of Simple and Annihilated Souls, by Marguerite Porete (1290). Since the work (and its author) was judged for heresy by the Inquisition (1310), it is intended to analyze it, through the method of bibliographic research, around the thesis that the construction of its subversive discourse in favor of the remodeling of the spiritual experience it took place through the strategic use of allegories in a context of oppression, taking advantage of the political potential of language. To this end, it starts from the idea that female subversion takes place on three levels: a) through the context; b) the speech; and c) the written word. Seeking to develop about the medieval female protagonism and authorship and to reveal the importance of the rescue of works of female authorship for the (re)construction of a History of women, it takes into account the mendicant movements and the propagation of the beguines, as well as medieval francophone social organization. In this sense, the analysis is developed based on the three main characters of the work, represented by female allegories: Soul, Love and Reason. Therefore, the research is based on studies about allegories and feminist studies, especially those proposed by Hansen (2006), Tambling (2010), Ricoeur (2015), Fletcher (1970), Newman (2005), Chance (2007), Rovere (2019) and Funck (2016), and in the historical studies proposed by Le Goff and Schmitt (2017), Pernoud (1996), Bloch (2016), Power (1979), Simons (2001), Lerner (1993), McGinn (2017), Dalarun (1990), Newman (1995), Delumeau (1978), Verdeyen (1986), Kocher (2008), Deane (2011), among others.